The transforms and appliactions handbook - Poularikas, Alexander D. (The electrical engineering handbook series, 1995)
The Transforms and Applications Handbook brings together in a single volume the most important mathematical transforms that are frequently used by engineers and scientists. Each chapter covers one of the transforms and provides numerous examples. These examples highlight the use of the transform and its properties. Applications to different areas are also included in each chapter.